Influence of Estrogen Modulation on Glia Activation in a Murine Model of Parkinson's Disease - Siani, Francesca; Greco, Rosaria; Levandis, Giovanna; Ghezzi, Cristina; Daviddi, Francesca; Demartini, Chiara; Vegeto, Elisabetta; Fuzzati-Armentero, Marie-Thérèse; Blandini, Fabio (Frontiers in Neuroscience, 2017)
Epidemiological data suggest a sexual dimorphism in Parkinson disease (PD), with women showing lower risk of developing PD. Vulnerability of the nigrostriatal pathway may be influenced by exposure to estrogenic stimulation throughout fertile life. To further address this issue, we analyzed the progression of nigrostriatal damage, microglia and astrocyte activation and microglia polarization triggered by intrastriatal injection of dopaminergic neurotoxin 6-hydroxydopamine (6-OHDA) in male, female and ovariectomized (OVX) mice, as well as in OVX mice supplemented with 17βestradiol (OVX+E). Animals were sacrificed at different time points following 6-OHDA injection and brain sections containing striatum and substantia nigra pars compacta (SNc) underwent immunohistochemistry for tyrosine hydroxylase (dopaminergic marker), immunofluorescence for IBA1 and GFAP (markers of microglia and astrocyte activation, respectively) and triple immunoflorescent to identify polarization of microglia toward the cytotoxic M1 (DAPI/IBA1/TNFα) or cytoprotective M2 (DAPI/IBA1/CD206) phenotype. SNc damage induced by 6-OHDA was significantly higher in OVX mice, as compared to all other experimental groups, at 7 and 14 days after surgery. Astrocyte activation was higher in OVX mice with respect the other experimental groups, at all time points. Microglial activation in the SNc was detected at earlier time points in male, female and OVX+E, while in OVX mice was detected at all time-points. Microglia polarization toward the M2, but not the M1, phenotype was detected in female and OVX+E mice, while the M1 phenotype was observed only in male and OVX mice. Our results support the protective effects of estrogens against nigrostriatal degeneration, suggesting that such effects may be mediated by an interaction with microglia, which tend to polarize preferentially toward an M2, cytoprotective phenotype in the presence of intense estrogenic stimulation.